2002
DOI: 10.1034/j.1600-079x.2002.01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute modifications in the levels of daytime melatonin do not influence leptin in postmenopausal women

Abstract: Melatonin shows a clear circadian rhythm with peak values at night, and may act directly with fat cells. Leptin, the anorexic hormone synthesized mainly by adipocytes, is produced in a circadian fashion, similar to that of melatonin. Accordingly, in the present study, we investigated whether melatonin may contribute to the rise in circulating leptin. The study was performed in postmenopausal women with 2 months of treatment with placebo or estradiol (50 microg/day). Melatonin was administered in doses of 1 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
3
17
1
1
Order By: Relevance
“…However, some studies have reported contradictory results in the possible relationship between MEL and LEP secretion [14]–[16], [33][35]. In our study, a significant negative correlation was established between MEL and LEP in the healthy animal while it did not exist in the AD animal.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…However, some studies have reported contradictory results in the possible relationship between MEL and LEP secretion [14]–[16], [33][35]. In our study, a significant negative correlation was established between MEL and LEP in the healthy animal while it did not exist in the AD animal.…”
Section: Discussioncontrasting
confidence: 40%
“…Despite the different circadian secretion patterns of leptin and melatonin, both hormones seem to be related although these results are controversial ones [14]–[16].…”
Section: Introductionmentioning
confidence: 99%
“…During the day, acute modifications in the levels of melatonin do not influence those of leptin in menopausal women, whether they are being treated with estradiol [46] or not, which confirms our findings about the absence of a correlation between these two hormones. While melatonin levels decreased in both sexes in the interval between the two evaluations made in our study, those of leptin remained practically unchanged during the interval of time in which puberty advanced one Tanner stage.…”
Section: Discussionsupporting
confidence: 81%
“…In most animal model studies, exogenous melatonin was found to decrease the circulating leptin levels [31, 33, 36]. In human studies, the results are inconsistent [83, 99, 100]. Herein, leptin levels remained unchanged after a 30-day low-calorie diet in both melatonin and placebo groups.…”
Section: Discussionmentioning
confidence: 99%